وسائل الإعلام والاتصال ودورها في تفعيل وتحسين أداء الجمعيات ومؤسسات المجتمع المدني في الجزائر - خضير, رشيد (جامعة الوادي - University of Eloued, 2021)
تناول هذه الدراسة أهمية دور الإعلام والاتصال في تحسين أداء الجمعيات ومؤسسات المجتمع المدني؛ وتوضح الدراسة وظائف الإعلام المختلفة؛ وتصنيفات الجمعيات وفقا لقانون الجمعيات 12-06؛ وطبيعة علاقتها بوسائل الإعلام. وتبرز الدراسة منح قانون الجمعيات 12-06، وقانون الإعلام 12-05 الجمعيات حق امتلاك وسائل الإعلام للتعبير عن رأيها وممارسة نشاطاتها تكريسا للحق الذي كفله الدستور لها. وتظهر الدارسة ضعف النشاط الإعلامي للجمعيات ومؤسسات المجتمع المدني، سواء من حيث توظيف وسائل الإعلام المختلفة، خاصة وسائط التواصل الاجتماعي، أو من حيث امتلاكها لوسائط الإعلام التقليدية من جرائد ومنشورات أو الجديدة من مواقع الانترنت ووسائط التواصل فايسبوك، اليوتيوب وغيرها. This study deals with the importance of information and communication in improving the performance of associations and civil society institutions. The study illustrates the various media functions and classifications of associations according to Associations Law 12-06 and the nature of its relationship with the media. The study highlights the granting of Associations Law 12-06 and Media Law 12-05 to associations the right to own media outlets to express their opinion and to presente their activities in consecration of the right guaranteed by the constitution to them. The study shows the weakness of the media activity of associations and civil society institutions, whether in terms of employing various media, especially social media, or in terms of their ownership of traditional media such as newspapers and publications, or new media; websites, social media, Facebook, YouTube.
media And Communication And Their Role In Activating And Improving The Performance Of Associations And Civil Society Institutions In Algeria
مقال
Keywords: وسائل الإعلام والاتصال؛ تحسين الأداء؛ الجمعيات؛ مؤسسات المجتمع المدني; Media and Communication; Improve the Performance; Associations; Institutions of Civil Society.